Form of Presentation of Calempong Oguang at Wedding Events in Sialang Kapur IX Lima Puluh Kota - Syeilendra; Melia Septri (Universitas Negeri Padang, 2023)
This This study aims to describe and find out about the form of presentation of Calempong Oguang art to the Sialang community. This type of research is a qualitative research with a descriptive analysis method approach. Types of data using primary data and secondary data. The main instrument is the researcher himself and assisted by supporting instruments such as stationery and cellphones. Data collection techniques were carried out by means of literature studies, observations, interviews, and documentation. The data analysis steps are data reduction, data display, and conclusion. The results of the study suggest that the form of presentation of the Calempong Oguang art to the Sialang community at weddings is in front of the house using the arena stage model. In this wedding event, songs were played at night: 1) Tigo-Tigo songs, 2) Lang Lalu songs, 3) Sandayuang songs, 4) Kaja Bakaja songs and others which began after the Isha prayer was finished around 08.00 WIB until dawn in the morning. The presentation of Calempong Oguang played by parents (male and female) in the form of a mixed ensemble aims to entertain the mothers who are cooking and the invited guests so they can relieve fatigue when preparing food for tomorrow's wedding day. With the sounds of Calempong Oguang songs, it is able to create a happy atmosphere and can bring closer ties with family and guests who come to the house.